Correlation Between Thyroid Nodules and Metabolic Syndrome: A Systematic Review and Meta-Analysis - Zhang, Chenyu; Gao, Xiaotong; Han, Yutong; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2021)
Objective Thyroid nodules (TNs) are a common thyroid disorder that can be caused by many factors. Several studies have investigated the relationship between TNs and metabolic syndrome (MetS), but the role of sex and age remains controversial. The purpose of this paper was to analyze published data from all relevant studies to reliably estimate the relationship between TNs and MetS. Methods Thirteen articles were included in this study; articles were identified by searching for publications until July 2021 in PubMed, EMBASE, the Cochrane Library and the Web of Science. The outcomes are presented as the summary odds ratio (OR) and 95% confidence interval (CI) and the pooled prevalence and 95% CI. Results The TNs prevalence was significantly higher in MetS patients than in controls (OR 1.88, 95% CI 1.42-2.50, P < 0.0001) and was independent of sex (male: OR 1.53, 95% CI 1.20-1.94, P = 0.0006; female: OR 1.90, 95% CI 1.54-2.33, P < 0.00001; combined: OR 2.06, 95% CI 1.31-3.25, P = 0.002) and age (< 40 years old: OR 1.62, 95% CI 1.39-1.89, P < 0.0001; 40 50 years old: OR 2.14, 95% CI 1.49-3.08, P < 0.0001;50 60 years old: OR 1.50, 95% CI 1.08-2.07, P = 0. 01; 60 years old: OR 1.70, 95% CI 1.36-2.14, P < 0.00001); the pooled TNs prevalence in MetS patients was 45% (95% CI 36-54%). However, it has not yet been considered that MetS is related to TNs in people with iodine deficiency (OR 3.14, 95% CI 0.92-10.73, P = 0.07). Conclusion The meta-analysis results showed a strong correlation between TNs and MetS. Both male and female patients with MetS had an increased TNs prevalence. In addition, the prevalence was independent of age. However, MetS is not considered to be associated with TNs in iodine-deficient populations.